4.75 mm SMA Performance and Cost-Effectiveness for Asphalt Thin Overlays. Issue Volume 17:Issued 9(2016) (20th October 2016) - Son, Songsu; Al-Qadi, Imad L.; Zehr, Tom
Abstract : This paper presents the design of stone matrix asphalt (SMA) with 4.75-mm nominal maximum aggregate size (NMAS) and alternative surfacing cross-section for an asphalt wearing course that may improve pavement performances while controlling costs by using locally available aggregates. The 4.75 -mm NMAS dense-graded mix was previously used in several states to reduce layer thickness and cost. Because of its poor friction and limited performance, however, it was generally used as levelling binder and placed on low-volume roads. The 4.75-mm SMA is proposed for thinner asphalt overlays in this study to improve its performance as well as surface texture. The ultimate goal of this study is to develop the 4.75-mm SMA and evaluate its performance and engineering benefits as a wearing course under laboratory and field conditions. Test pavement sections were constructed in Northern Illinois and on-site performance tests were conducted to evaluate its performance under actual traffic loading. The engineering cost-benefit analysis with respect to performances from both laboratory and field studies suggests the proper application of 4.75-mm SMA as an efficient and cost-effective wearing course for asphalt thin overlays.